PELATIHAN PENGEMBANGAN PERMAINAN TRADISIONAL ULAR TANGGA DALAM PEMBELAJARAN MATEMATIKA KELAS 4 SD NEGERI GUNUNG SARI - Feny Nida Fitriyani; Zubaidi Zubaidi; Miftachudin Miftachudin; Nurmaidah; Rheina Nisa Az Zahra; Faridatul Fikriyyah (Fakultas Tarbiyah dan Keguruan, 2025)
Community service activities in the form of training on the development of traditional snake and ladder games as a mathematics learning medium in grade IV of SD Negeri Gunung Sari have had a significant impact on improving the quality of learning. The training aims to introduce an innovative approach to teaching mathematical concepts through the integration of modified traditional games with contextual problems. The results showed that students experienced a significant increase in interest in learning and understanding of mathematics materials. The enthusiasm and active participation of students during the learning process reflect the success of this method in creating a fun, interactive, and non-boring learning atmosphere. The modified snake and ladder game has proven to be an effective medium in overcoming learning boredom and encouraging collaboration between students. In addition to having a positive impact on students, this training also provides benefits for teachers in terms of improving pedagogic competence. Teachers feel more confident and motivated to develop and implement creative and contextual learning media according to student characteristics. Furthermore, the use of traditional games as a learning medium also contributes to the preservation of local culture, so that students not only gain academic knowledge, but also cultural values inherent in people's lives. Thus, this activity not only enriches mathematics learning strategies in elementary schools, but also becomes the first step in building synergy between modern education and local wisdom in a sustainable manner.